Creep behaviour of inconel 718 processed by laser powder bed fusion - Xu, Zhengkai; Hyde, C.J.; Tuck, C.; Clare, A.T. (Elsevier, 2018)
Additive manufacturing lends itself well to the manufacture of aerospace parts due to the high complexity and small volume of many components found in modern aero engines. By exploiting additive manufacturing design freedoms, enhanced part functionality can be achieved and lead time can be reduced. However, the integrity of these parts is a primary concern which often cannot be guaranteed with current generation additive manufacturing methods and materials. Studies on the performance of additively manufactured parts under service conditions are therefore required.